Software Synthesis Procedures. - Kuncak, Viktor; Mayer, Mikaël; Piskac, Ruzica; Suter, Philippe (Communications of the ACM, 2012)
Automated synthesis of program fragments from specifications can make programs easier to write and easier to reason about. To integrate synthesis into programming languages, software synthesis algorithms should behave in a predictable way: they should succeed for a well-defined class of specifications. We propose to systematically generalize decision procedures into synthesis procedures, and use them to compile implicitly specified computations embedded inside functional and imperative programs. Synthesis procedures are predictable, because they are guaranteed to find code that satisfies the specification whenever such code exists. To illustrate our method, we derive synthesis procedures by extending quantifier elimination algorithms for integer arithmetic and set data structures. We then show that an implementation of such synthesis procedures can extend a compiler to support implicit value definitions and advanced pattern matching.